Haunted by chaos : China's grand strategy from Mao Zedong to Xi Jinping - Khan, Sulmaan Wasif (Harvard University Press, 2018)
Sulmaan Khan examines the concerns that have shaped China's decision-making on the world stage. He compares the grand strategies of Mao Zedong, Deng Xiaoping, Jiang Zemin, Hu Jintao, and Xi Jinping, analyzing what goals they had for China, their plans for achieving them, and how well their strategies worked. Khan argues that from Mao to Xi there has been a consistent definition of national goals and a harnessing of military, diplomatic, and economic means to pursue those aims. Khan is not suggesting there was a well-crafted master plan from the beginning of the People's Republic of China, but he finds a common purpose and vision for China across these leaders: they all saw China as a brittle entity in a world that was fundamentally dangerous. Their objective was not only to protect China in such a world, but to ensure that it never again felt as powerless as it had in the late Qing and early Republic era. Ranging from the Tibetan plateau to the South China Sea, from China's time as a global pariah to bastion of the world economy, this is the first comprehensive account of the grand strategies of the People's Republic of China. For all their considerable costs, these strategies have, for the most part, been successful. But the very forces that made China whole and strong now risk tearing it back apart. Khan concludes with the great challenges facing Chinese strategists today. The population is aging, and the costs of global warming and environmental change could prove catastrophic. Life on a day-to-day basis is richer, but more precarious. Economic influence might be spreading, but air quality is bad and people cannot trust food grown on poisoned land. Going forward, China's leaders will seek solutions to such long-term problems that could affect national security.--